FRI0307 The association between pain and ultrasonographic features of hand osteoarthritis in finger joints. (23rd January 2014) - Mathiessen, A.; Haugen, I.K.; Slatkowsky-Christensen, B.; Kvien, T.K.; Hammer, H.B.
Abstract : Background: Hand osteoarthritis (HOA) may cause considerable pain, but the sources of pain are still unclear. Radiographic OA features show only a modest association with symptoms in HOA and association between ultrasonography (US) findings and clinical symptoms/findings have not been sufficiently explored. Objectives: To investigate whether US-detected structural and inflammatory abnormalities are associated with pain in the same joint in HOA. Methods: We included 127 HOA patients (116 women, mean (SD) age 68.6 (5.8) years and disease duration 18.3 (7.2) years) with ultrasonographic and clinical examination of both hands. The US examination (Siemens Antares, 5-13MHz) included assessment of osteophytes, grey scale synovitis and power Doppler (PD) in the 1st carpometacarpal (CMC), first interphalangeal, 2nd-5th proximal (PIP) and distal interphalangeal (DIP) joints using a dorsal view from radial to ulnar side bilaterally. The same joints were examined clinically for tenderness upon palpation. We calculated the odds ratio (95% confidence interval) for tenderness in joints in which US pathology was present (with joints without US pathology as reference) by Generalized Estimating Equations in order to adjust for within-subject dependency using an exchangeable covariance matrix. The US features were then included in a multivariate model in order to assess the independent associations for each feature. Finally, we tested the multivariate model in the different joint groups separately. All analyses were adjusted for age and sex. Results: In the 2510 joints examined, we found high prevalence of osteophytes (n=1840), whereas lower prevalence of synovitis (n=560) and especially PD activity (n=72). There were significantly higher odds of tenderness in joints with all types of US pathology (table ). Multivariate analyses provided the same results (table). Osteophytes and synovitis were more strongly associated with tenderness in the 1st CMC joints, while power Doppler signal was more strongly associated with tenderness in the PIP-joints. Higher scores of all US features were dose-dependently associated with tenderness in joints (data not shown). Conclusions: Osteophytes, synovitis and power Doppler signal detected by US were independently and dose-dependently associated with joint tenderness in individual HOA joints. These findings are relevant for our understanding of the etiology of pain in HOA. Disclosure of Interest: None Declared